2016
DOI: 10.1016/s1470-2045(16)30166-8
|View full text |Cite
|
Sign up to set email alerts
|

Vemurafenib in patients with BRAFV600E-positive metastatic or unresectable papillary thyroid cancer refractory to radioactive iodine: a non-randomised, multicentre, open-label, phase 2 trial

Abstract: Summary Background About half of patients with papillary thyroid cancer have tumours with activating BRAFV600E mutations. Vemurafenib, an oncogenic BRAF kinase inhibitor approved for BRAF-positive melanoma, showed clinical benefit in three patients with BRAFV600E-positive papillary thyroid cancer in a phase 1 trial. We aimed to establish the activity of vemurafenib in patients with BRAFV600E-positive papillary thyroid cancer. Methods We did an open-label, non-randomised, phase 2 trial at ten academic centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
214
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(228 citation statements)
references
References 24 publications
5
214
0
9
Order By: Relevance
“…The presence of BRAF mutation was an inclusion criterion in phase 2 trials with a BRAF inhibitor, either 297 vemurafenib or dabrafenib (Brose, et al 2016;Dadu, et al 2015;Falchook, et al 2015) and positive results 298 were observed, and these results may be improved by a combination with a MEK inhibitor. Mutation in ALK 299 (Anaplastic Lymphoma Kinase) gene has been reported in few patients with refractory DTC and can be the 300 target of an ALK inhibitor (Kelly, et al 2014).…”
Section: Drugs Directed Against Other Targets 292mentioning
confidence: 99%
“…The presence of BRAF mutation was an inclusion criterion in phase 2 trials with a BRAF inhibitor, either 297 vemurafenib or dabrafenib (Brose, et al 2016;Dadu, et al 2015;Falchook, et al 2015) and positive results 298 were observed, and these results may be improved by a combination with a MEK inhibitor. Mutation in ALK 299 (Anaplastic Lymphoma Kinase) gene has been reported in few patients with refractory DTC and can be the 300 target of an ALK inhibitor (Kelly, et al 2014).…”
Section: Drugs Directed Against Other Targets 292mentioning
confidence: 99%
“…These include the selective BRAF V600E inhibitors dabrafenib and vemurafenib. Although these agents are currently approved for use in patients with melanoma, their safety and efficacy have been reported in patients with metastatic RAI-refractory DTC (20,21). These TKIs have been shown to have clinical benefit without reports of fistula development, and work through inhibition of the mutated BRAF kinase commonly seen in patients with DTC.…”
Section: Discussionmentioning
confidence: 99%
“…Severe AEs were noted in 65 and 68% of the two groups, respectively, [29,48] with 22% developing cutaneous squamous cell carcinoma [28,30].…”
Section: Braf Inhibitorsmentioning
confidence: 99%
“…Vemurafenib was efficient in some BRAFV600E-positive advanced RAIRTC patients (partial responses of 35-38.5% in naive patients and 26-29% in those previously exposed to a VEGFR inhibitor) [29][30][48][49]. Severe AEs were noted in 65 and 68% of the two groups, respectively, [29,48] with 22% developing cutaneous squamous cell carcinoma [28,30].…”
Section: Braf Inhibitorsmentioning
confidence: 99%